2022
DOI: 10.1039/d2fo02598a
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin alleviates LPS-induced intestinal homeostatic imbalance through reshaping gut microbiota structure and regulating group 3 innate lymphoid cells in chickens

Abstract: Curcumin could be used as a modulator of gut microbiota for intestinal health improvement and immunity homeostasis via modulation of the BA-FXR pathway and ILC3s function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In turn, the TCA cycle can also influence amino acid and lipid metabolism through the synthesis of metabolites. Ruan, et al (2022) reported that LPS attack resulted in an imbalance in broiler intestinal homeostasis with changes in the levels of metabolites related to energy metabolism, including reduced concentrations of butyric acid, 3-hydroxybutyric acid, malic acid, and succinic acid, and increased levels of alanine. Zhao et al (2022) found that LPS produced 3 breakpoints in the TCA cycle of macrophages, namely, downregulation of isocitrate dehydrogenase, inhibition of succinate accumulation and SDH activity, and a significant decrease in the expression level of carboglutarate dehydrogenase and its substrate α-ketoglutarate.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the TCA cycle can also influence amino acid and lipid metabolism through the synthesis of metabolites. Ruan, et al (2022) reported that LPS attack resulted in an imbalance in broiler intestinal homeostasis with changes in the levels of metabolites related to energy metabolism, including reduced concentrations of butyric acid, 3-hydroxybutyric acid, malic acid, and succinic acid, and increased levels of alanine. Zhao et al (2022) found that LPS produced 3 breakpoints in the TCA cycle of macrophages, namely, downregulation of isocitrate dehydrogenase, inhibition of succinate accumulation and SDH activity, and a significant decrease in the expression level of carboglutarate dehydrogenase and its substrate α-ketoglutarate.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that 250 mg/kg CUR supplementation increased body weight, ADG and ADFI in genotype AA commercial broilers at 21 and 42 days of age, and significantly reduced FCR [ 20 ]. The CUR supplementation at 300 mg/kg increased ADG during days 1–21, regardless of LPS stimulation [ 21 ]. In our study, CUR supplementation had no significant effect on growth performance, and neither PE nor CUR addition had a significant effect on ADFI and FCR.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, lithocholic acid (LCA) ameliorated the TNF-α-induced distribution of ZO-1, E-cadherin, occludin, and claudin-1 [15]. The administration of curcumin, a polyphenolic compound isolated from turmeric, decreased the lipopolysaccharides (LPS)-induced injury of intestinal tight junctions and alleviated acute inflammation in the mucosa, likely through altering the microbiome and modulation of bile acid metabolism [16]. .…”
Section: Bile Acids and Intestinal Epithelial Cells Tight Junctionsmentioning
confidence: 99%